Association between personality traits and concerns about falling among older patients: the mediating role of subjective age - Fan, Rongrong; Wang, Lili; Wang, Wenxiu; Zhong, Yanan; Zhang, Tingting; Yang, Xia; Zhu, Jing (Frontiers in Public Health, 2024)
Background Old patients are at high risk of falling, and regular assessments of their concerns about falling (CaF) are recommended. The present study aimed to investigate the correlation between CaF and personality traits among older patients as well as to elucidate the mediating role of subjective age.Method A cross-sectional study was conducted among patients aged over 60 years in a tertiary hospital located in Chengdu, Sichuan Province, from March 2023 to May 2023. Predesigned electronic questionnaires were distributed to collect relevant data. Four different models (both crude and adjusted weighted linear regression models) were constructed based on the confounders.Confounders were gradually put into the models to control for bias and to examine the stability of the correlations. Bootstrap sampling was employed to examine the mediating role of subjective age.Results A total of 407 patients were included. According to the fully adjusted model, neuroticism (β = 0.17, 95% CI: 0.02 to 0.31, p for trend = 0.02), extraversion (β = -0.07, 95% CI: -0.15 to 0.001, p for trend = 0.05), and subjective age (β = 2.02, 95% CI: 1.28 to 2.78, p for trend < 0.001) were consistently correlated with CaF. Subjective age was found to be a partial mediator (23.2%) of the relationship between extraversion and CaF. Higher neuroticism (β = 0.002, 95% CI: 0.001 to 0.004, p for trend = 0.006) was related to older subjective age, while higher levels of conscientiousness (β = -0.002, 95% CI: -0.004 to 0.00, p for trend = 0.04), openness (β = -0.003, 95% CI: -0.01 to 0.001, p for trend = 0.003), and extraversion (β = -0.002, 95% CI: -0.00 to -0.00, p for trend = 0.0) were correlated with younger subjective age.Extraversion and neuroticism were significantly correlated with CaF. Moreover, subjective age partially mediated the relationship between extraversion and CaF. Furthermore, subjective age was found to be associated with both CaF and personality traits. These findings highlighted the important roles of personality traits and subjective age in assessments of CaF and in the development of strategies for preventing falls among older patients.